2018
DOI: 10.1126/science.aao3264
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved gene family encodes proton-selective ion channels

Abstract: Ion channels form the basis for cellular electrical signaling. Despite the scores of genetically identified ion channels selective for other monatomic ions, only one type of proton-selective ion channel has been found in eukaryotic cells. By comparative transcriptome analysis of mouse taste receptor cells, we identified Otopetrin1 (OTOP1), a protein required for development of gravity-sensing otoconia in the vestibular system, as forming a proton-selective ion channel. We found that murine OTOP1 is enriched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
218
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(256 citation statements)
references
References 34 publications
7
218
0
Order By: Relevance
“…Type II TRCs express different G-protein coupled receptors (GPCRs), which transduce sweet, bitter, and umami taste qualities (Adler et al 2000; Mueller et al 2005; Nelson et al 2002; Nelson et al 2001; Zhang et al 2003; Zhao et al 2003). The final cell type, Type III TRCs, detect sour tastants via cytoplasmic changes in pH (Huang et al 2008; Ishimaru et al 2006; Tu et al 2018). While many genetic and electrophysiological studies have been conducted on the gustatory system, substantially less data on the TRC transcriptome is available.…”
Section: Introductionmentioning
confidence: 99%
“…Type II TRCs express different G-protein coupled receptors (GPCRs), which transduce sweet, bitter, and umami taste qualities (Adler et al 2000; Mueller et al 2005; Nelson et al 2002; Nelson et al 2001; Zhang et al 2003; Zhao et al 2003). The final cell type, Type III TRCs, detect sour tastants via cytoplasmic changes in pH (Huang et al 2008; Ishimaru et al 2006; Tu et al 2018). While many genetic and electrophysiological studies have been conducted on the gustatory system, substantially less data on the TRC transcriptome is available.…”
Section: Introductionmentioning
confidence: 99%
“…A separate study reported that Type III cells are heterogeneous and do not uniformly express the same cell markers (Courtney E Wilson, 2017), so it may be that the BR cells are separate from the PKD2L1 expressing Type III cells. Recently, OTOP1, which is expressed in Type III taste cells, has been proposed as the sour receptor (Teng, Wilson et al, 2019, Tu, Cooper et al, 2018, Zhang et al, 2019). Nerve recordings from OTOP1-KO mice were significantly reduced for sour stimuli but also showed some reduction in their responsiveness to bitter, sweet and umami (Teng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their broad roles in biology, knowledge of proton channels has lagged behind that of other types of ion channels. The recent characterization of Otopetrins, previously implicated in vestibular function 11,12 , provides impetus for investigations of this novel proton channel family 10…”
Section: Discussionmentioning
confidence: 99%
“…Because they were only recently characterized, the physiological roles of Otopetrins are just now beginning to be uncovered. Notably, Otop1 is required for proton currents in murine cells that detect sour taste and is a likely candidate for a sour taste receptor [4][5][6]10 . In addition, prior genetic studies identified Otop1 as the gene mutated in a spontaneously occurring vestibular disorder in mice and required in the vestibular system for normal otoconia development in mice 11 and zebrafish 12,13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation